Answer:
If that is supposed to say she sold 5 DOZEN eggs at the farmer's market then The farmer gave away 7 dozen eggs which would be 84 eggs. She earned $22.50
Step-by-step explanation:
12 dozen - 5 dozen = 7 dozen
7 dozen x 12 = 84 eggs
5 dozen x 4.50 = $22.50
Answer:
J, 6
Step-by-step explanation:
plug in the values given into the equation
x = 5 and y = 2
4(5) - (2)³/ 2
20 - 8/2
20 - 8 = 18
12/2
6
the value of
is 6 when the values are plugged in
Answer:
No solutions
Step-by-step explanation:
![9^x + 4(3^x + 1) + 27 = 0\\3^{2x} + 4 \cdot 3^x + 31 = 0](https://tex.z-dn.net/?f=9%5Ex%20%2B%204%283%5Ex%20%2B%201%29%20%2B%2027%20%3D%200%5C%5C3%5E%7B2x%7D%20%2B%204%20%5Ccdot%203%5Ex%20%2B%2031%20%3D%200)
Substitute 3^x with t and we get.
![t^2 + 4t + 31 = 0\\\triangle = 16 - 4 \cdot 31 = -108 < 0 => t_{12} \notin R => x \notin R](https://tex.z-dn.net/?f=t%5E2%20%2B%204t%20%2B%2031%20%3D%200%5C%5C%5Ctriangle%20%3D%2016%20-%204%20%5Ccdot%2031%20%3D%20-108%20%3C%200%20%3D%3E%20t_%7B12%7D%20%5Cnotin%20R%20%3D%3E%20x%20%5Cnotin%20R)
Answer:
Step-by-step explanation:
75+ 25x
75+25(4)
75+100
175
Answer:
f'(x) = -f(x) = 9xy² - 6x²y + 5x³
Step-by-step explanation:
f(x) = –9xy² + 6x²y – 5x³
additive inverse: f'(x) = -f(x) = 9xy² - 6x²y + 5x³
f(x) + f'(x) = f(x) -f(x) = (–9xy² + 6x²y – 5x³) + (9xy² - 6x²y + 5x³) = 0